Analisis Konjungsi Shitagatte dan Yue Ni dalam Website Surat Kabar Bahasa Jepang Asahi.Com - Felicia Felicia (Bina Nusantara University, 2010)
In studying the Japanese language there are many things that must be understood such as verbs, particles, adjectives and conjunctions. From existing various conjunctions, the author conducted an analysis of the conjunctions yue ni and shitagatte which has the same meaning but different in its use. The research method used was literature research method is to retrieve data from the Japanese newspaper website asahi.com. The purpose of this study is to investigate the function of conjunctions yue ni and shitagatte and know when to use shitagatte and when to use yue ni. After conducting an analysis of the 3 articles in which contains shitagatte and 3 articles in which contains yue ni, the authors conclude that the sentence after shitagatte only emphasize on the effect or outcome of the sentence before shitagatte, while on sentences after yue ni, in addition to a result or the results also contained elements of desire.